Transportation Management Plan of Haifa, Jaffa, and Tunis streets area - Tamer Sami Isawi; Amr Shaker Bitar; Amjad Amir Amir; Mohammed Kamel Abdul-Hadi (My University, 2018)
Haifa, Jaffa and Tunis streets are important streets in Nablus city. They have heavy traffic volume almost all day long. These and their surrounding areas are expected to grow and develop at a fast rate in the future, and expected to have emerging problems due to this growth. Therefore, it is important to shed a light on the problem, find the causes, and find some viable solutions so that competent authorities may apply these solutions as much as possible. This study focuses on: 1. Traffic operating conditions. 2. Pavement conditions. 3. Geometric design of the streets in the area. 4. Proposing ideas and solutions for existing and forecasted problems. The methodology that gas been conducted in this study is based on previous studies in this area, as well as using techniques, methods, and references adopted locally and internationally. Our team made field visits to considered area – as we as described previously – to report the state of the street, and collect field data on the traffic operating conditions obtained from the analysis phase, the proper design and management plan have been made. The analysis and designs were based on American Association of State Highway and Transportation Officials (AASHTOO), Highway Capacity Manual and local specifications and standards. Finally, the work done was performed in a report with the necessary design plans, tables, figures and proposed solutions. Results of the study are provided in this project include traffic conditions, geometric designs, and pavement designs need to be revised and redesigned in order to improve traffic conditions and reduce overcrowding level. It also includes improving traffic safety conditions for the study area. Furthermore, pavement conditions and riding comfort need to be revised too. The results of this study will also be useful for future studies as well. The final output will form a transportation management plan for the study area along with plans and ideas on improving the existing conditions in order to provide the best possible outcomes and solutions for forecaster problems.